PEMBELAJARAN GI DAN GI-PROBLEM POSING (GI-PP) PADA MATA KULIAH KALKULUS LANJUT DITINJAU DARI SIKAP MAHASISWA TERHADAP MATEMATIKA - Swasti Maharani (Universitas PGRI Madiun, 2015)
The objectives of this research were to find out: (1) which learning model of the GI or GI-ProblemPosing results in a better learning achievement; (2) which students’ attitudes of the positive, neutral, or negative types results in a better learning achievement; (3) in each students’ attitudes, which learning model of the GI or GI-Problem Posing results in a better learning achievement; and (4) in each learning model, which students’ attitudes of the positive, neutral, or negative types results in a better learning achievement. This research used the quasi experimental research method with the factorial design of 2x3. Its population was all of the students of Mathematics department of IKIP PGRI Madiun in academic year 2014/2015. The samples were taken by using the random sampling technique. The data were gathered through test and questionnaire method and its were analyzed by using the unbalanced twoway analysis of variance at the significance level of 5%. The results showed that: (1) the GI and GI-ProblemPosing result in the same good learning achievement; (2) the learning achievement with positive was better than that with neutral and negative, that with neutral was better than that with negative; (3) in each students’ attitudes type, the GI and GI-ProblemPosing result in the same good learning achievement; (4) in general, the learning achievement with positive was better than neutral and negative, that neutral was better than negative. However, if viewed from GI with a positive and neutral have the same achievement and better than negative.